ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2014å±Šå¦ç”Ÿ ä½¿ç”¨â€œæ»¡è¶³â€å’Œâ€œæ»¡æ„â€çš„åè¯¯åˆ†æž - Fitrianingsih, Bella; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractGrammar is the rules of how to use words. Grammar is also one of the three elements of language. In Chinese, you will learn parts of speech such as verb, noun, adjective, adverb, preposition, conjunction,etc. Each part of speech has its own usage. Many Chinese words have similar meanings, such as